2022
DOI: 10.1007/s12310-021-09494-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Response and Management of Self-harm in School Children Under 13 Years of Age: A Qualitative Study

Abstract: Research suggests that the incidents of self-harm among young people are increasing and age of onset of self-harm is decreasing. There is limited understanding of how widespread the problem of self-harm among younger school students is, and how schools respond to these incidents. This study used an in-depth qualitative approach to understand self-harm in children under 13, and how elementary schools respond including typical actions, support for the child and parental involvement. School psychologists in New S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
2
1
0
1
Order By: Relevance
“…Existing strategies have shown some benefits in preventing suicidal ideation and self-harming behaviours in school during adolescence 55,56 (eg, awareness and skills training) and for at-risk youths (eg, dialectical behavioural therapy, cognitive behavioural therapy, and youth-nominated support teams), but it is unclear whether such interventions are developmentally appropriate for children younger than 12 years. In the meantime, our study, in line with others, 57 highlights the need for further support staff in schools, as well as awareness among paediatricians and others working with children, to recognise and address suicidal risk. Children might not disclose to their parents and might therefore not receive adequate and appropriate professional support.…”
Section: Discussionsupporting
confidence: 84%
“…Existing strategies have shown some benefits in preventing suicidal ideation and self-harming behaviours in school during adolescence 55,56 (eg, awareness and skills training) and for at-risk youths (eg, dialectical behavioural therapy, cognitive behavioural therapy, and youth-nominated support teams), but it is unclear whether such interventions are developmentally appropriate for children younger than 12 years. In the meantime, our study, in line with others, 57 highlights the need for further support staff in schools, as well as awareness among paediatricians and others working with children, to recognise and address suicidal risk. Children might not disclose to their parents and might therefore not receive adequate and appropriate professional support.…”
Section: Discussionsupporting
confidence: 84%
“…In line with current government frameworks, we propose that eLearning may be embedded as part of a wider program identifying and supporting mental health in YP attending secondary schools. In line with other authors suggestions (Townsend et al, 2022), we anticipate that eLearning may support in the upskilling of teachers, and additional members of school staff, and reduce the rates of selfharm in YP as well as increasing confidence in talking to YP on sensitive topics but further work is required.…”
Section: Discussionsupporting
confidence: 79%
“…(Sheftall et al, 2021). Self-harm, which was also found to correlate with suicidal thoughts and behavior among children (Hawton et al, 2012), serves as a coping mechanism to address di culties with, among other factors, anxiety and stress (Townsend et al, 2022). Moreover, studies indicated traits characterizing children who died by suicide, for example intelligence, aggression, mistrustfulness, social isolation and children who were sensitive to criticism (Soole et al, 2015).…”
Section: Introductionmentioning
confidence: 99%